Odpowiedzi

Najlepsza Odpowiedź!
2010-02-09T19:21:57+01:00
A) 5x(x-3)
b) 3b(y-2)
c) 8x(1-y)
d) 2a(5a-b)
e) xy(1-x)
f) 6(a-4b+5c)
g) 4b(3ab+4b)
h) x(X^2-2x+1)
i) x(2y+3-xy)
3 5 3
2010-02-09T19:22:33+01:00
A) 5x²-15x= 5x(x-3)
b) 3by-6b=3b(y-2)
c) -8xy+8x=8x(-y+1)
d) 10a²-2ab=2a(5a-b)
e) xy-x²y=xy(1-x)
f) 6a-24b+30c=6(a-4b+5c)
g) 12ab²+16b²=4b²(3a+4)
h) x³-2x²+x=x(x²-2x+1)
i) 2xy+3x-x²y=x(2y+3-xy)
1 5 1
2010-02-09T19:22:36+01:00
A) 5x²-15x=5x(x-3)
b) 3by-6b=3b(y-2)
c) -8xy+8x=-8x(y-1)
d) 10a²-2ab=2a(5a-b)
e) xy-x²y=xy(1-x)
f) 6a-24b+30c=6(a-4b+5c)
g) 12ab²+16b²=4b²(3a+4b)
h) x³-2x²+x=x(x²-2x+1)=x(x-1)²
i) 2xy+3x-x²y=x(2y+3-xy)
1 3 1